2018
DOI: 10.1007/s11892-018-1053-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Severe Obesity

Abstract: Purpose of ReviewThis review aims to present current information on genes underlying severe obesity, with the main emphasis on the three genes LEP, LEPR and MC4R.Recent FindingsThere is a substantial amount of evidence that variants in at least ten different genes are the cause of severe monogenic obesity. The majority of these are involved in the leptin-melanocortin signalling pathway. Due to the frequency of some of the identified variants, it is clear that monogenic variants also make a significant contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 109 publications
(114 reference statements)
0
44
0
4
Order By: Relevance
“…Obesity linked to heterozygous variants of the MC4R gene represents approximately 2-3% of severe obesity in children and adults, with more than 166 different functional variants described in various populations (Europeans, Americans, Asians) (36). Children with heterozygous variants have more body fat than non-mutated BMI-matched subjects (37). It was initially reported that they are taller in the first 5 years of life (27) and more hyperphagic, but these characteristics may decrease with age.…”
Section: Clinical Subtypes Of Genetic Obesitymentioning
confidence: 99%
“…Obesity linked to heterozygous variants of the MC4R gene represents approximately 2-3% of severe obesity in children and adults, with more than 166 different functional variants described in various populations (Europeans, Americans, Asians) (36). Children with heterozygous variants have more body fat than non-mutated BMI-matched subjects (37). It was initially reported that they are taller in the first 5 years of life (27) and more hyperphagic, but these characteristics may decrease with age.…”
Section: Clinical Subtypes Of Genetic Obesitymentioning
confidence: 99%
“…Severe obesity is known to be BMI with >35 kg/m 2 ; consists of obese I-IV ( Table 1 ). BMI is the only the tool used to evaluate frequencies of obesity in the adult-world population connected with health ( Fairbrother et al, 2018 ). Obesity associated diseases and disorders are amongst the leading cause of morbidity and mortality throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the discovery that several rare forms of obesity, called monogenic obesity, result from a mutation in single genes primarily located in the leptin–melanocortin pathway [15,16], recent evidence has identified additional selected genes associated with obesity, providing that the genetic background can play a pivotal role in causing or triggering susceptibility to the pathology when associated with environmental factors such as overeating and PE reduction [17,18]. Of note, brain-derived neurotrophic factor ( BDNF ) is included among these genes.…”
Section: Introductionmentioning
confidence: 99%